Caregiver burden in children with cystic fibrosis and primary ciliary dyskinesia - KARADAĞ, BÜLENT TANER; ERDEM ERALP, ELA; KARADAĞ SAYGI, NAİME EVRİM; KENİŞ COŞKUN, ÖZGE; GÖKDEMİR, YASEMİN (WILEY, 2019)
Introduction Caregiver burden impacts both the social and economic framework of society. Cystic fibrosis (CF) causes significant caregiver burden, but the current data is scarce. In the case of primary ciliary dyskinesia (PCD), even less is known. This study aims to compare the caregiver burden of the parents of patients with CF and PCD. Methods Patients with CF and PCD between the ages of 6 to 13 and their parents were included. Patients' clinical information and parents' demographics were recorded. Caregiver burden was measured with Zarit Caregiver Burden Scale (ZCB), while the quality of life (QOL) was measured with CFQOL-revised (CFQOL-R) and PCD QOL questionnaire as the patients' age and diagnosis indicated. Results A total of 63 patients, 44 with CF (69%) and 85 caregivers (35 mothers, 6 fathers, and 22 mother-father dyads) participated in the study. Caregiver burden was significantly higher in mothers of the CF group with a mean ZCB of 30.5 +/- 10.7 when compared to the PCD group with a mean ZCB of 21.93 +/- 8.26 (P = .006). This was similar in fathers with mean ZCB of 27.5 +/- 9.21 in the CF group and 20.36 +/- 7.43 in the PCD group (P = .03). In correlation analyses, mothers' caregiver burden moderately and inversely correlated with CFQOL-R subscales in the CF population. Conclusion Caregiver burden is significantly higher in the CF population when compared to PCD. It is correlated with pulmonary functions and QOL in patients with CF.
Keywords: caregiver burden; cystic fibrosis; primary ciliary dyskinesia; quality of life; ADOLESCENTS; DIAGNOSIS; PARENTS